Loneliness and internet addiction in doctors and medical students: a cross-sectional study - Ardiç, Cüneyt; İnecikli, Sibel and Hatipoğlu, Celile (International Journal of Research in Medical Sciences, 2018)
Background: Our aim in this study is to determine the level of internet addiction in medical school students and primary care physicians and the factors affecting them. Methods: A 68 physicians and 167 students participated in this descriptive study. The participants were administered the young ınternet addiction test, UCLA loneliness scale and asked to respond to survey questions about their ssociodemographic characteristics, and the relations were evaluated with appropriate statistical methods. Results: It has been identified that playing games online, surfing the internet aimlessly and loneliness score affected internet addiction regardless of other variables (p<0.05). A statistically significant correlation between addiction level and age (r= (-0.341), p<0,001), loneliness score (r=0,284, p<0,001) and online time (r=0,387, p<0,001) has been discovered. Conclusions: In this study, it was found statistically significant that students with internet addiction stayed online for long periods of time and it seemed in line with the criteria observed in substance use disorders such as longer duration of use than intended and not being able to spare time for other activities.